Salmonella enteridis Septic Arthritis: A Report of Two Cases - Esat Uygur; Krishna Reddy; Feyza Ünlü Özkan; Salih Söylemez; Özlem Aydin; Serkan Şenol (Case Reports in Infectious Diseases)
Introduction. Nontyphoidal salmonellosis causes significant morbidity, is transmitted via fecal-oral route, and is a worldwide cause of gastroenteritis, bacteremia, and local infections. Salmonella is a less common etiologic factor for septic arthritis compared with other gram-negative bacteria. Cases. We present two septic arthritis cases with Salmonella enteridis as a confirmed pathogen and also discuss the predisposing factors and treatment. Discussion. Septic arthritis is an orthopedic emergency. The gold standard treatment of septic arthritis is joint debridement, antibiotic therapy according to the culture results, and physiotherapy, which should start in the early postoperative period to prevent limitation of motion. Salmonella is an atypical agent for septic arthritis. It must be particularly kept in mind as an etiologic factor for the acute arthritis of a patient with sickle cell anemia and systemic lupus erythematosus. Clinicians should be cautious that the white blood cell count in synovial fluid can be under 50.000/mm3 in immune compromised individuals with septic arthritis. The inflammatory response can be deficient, or the microorganism may be atypical. Conclusion. Atypical bacteria such as Salmonella species in immune compromised patients can cause joint infections. Therefore, Salmonella species must always be kept in mind for the differential diagnosis of septic arthritis in a clinically relevant setting.